Products or markets: What type of experience matters for export survival? - Martina Lawless; Zuzanna Studnicka (University College Dublin, UCD Centre for Economic Research, 2019)
Previous research has generally shown that increased export experience has a positive impact on the subsequent survival of newly launched export relationships of a firm. In this paper, we find that there are important differences in the effects of firm experience on export survival depending on the source of the experience. Specifically, experience built up by a firm from previously exporting a particular product before launching it in a new market has a strong positive impact on the survival of a new product-market relationship. In contrast, experience within a market prior to adding a new product has a mainly negative effect on the survival probability of the additional product. This shows that taking a successful product to new markets is more likely to succeed than expanding product range within a market.
Keywords: F10; 330; Duration of Trade; Firm Survival; Export Experience; Multi-product firms